Freedom Communications, Inc : family enterprise or liquidity? - Ward, John L., 1945-; Zsolnay, Carol (London : Kellogg School of Management, 2007)
The case explains the complex divisions and ownership of Freedom Communications Inc. by the Hoiles family and the different options the family shareholders must explore for liquidating their individual shares of the company.
Originally published in Ward, J., & Zsolnay, C. (2007). Freedom Communications, Inc: Family enterprise or liquidity? 5-307-504. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Freedom Communications (Irvine, Calif.) -- Case studies; Stockholders -- United States -- Case studies; Family-owned business enterprises -- United States -- Case studies